Intrinsic Mobility by Acoustic Phonon Scattering of Two Dimensional Semiconductors (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and determined the intrinsic mobility by acoustic phonon scattering which  provided on important upper limit for the available motilities. In the low temperature regime,  acoustic phonon dominated transport manifested itself in a strong change in the temperature  dependence of the carrier mobility once the temperature is lowered below the Bloch Gruneisen temperature. For Hetrostructure based two dimensional electron gas the Bloch Gruneisen regime was well established. In a two dimensional electron gas the Fermi wave  vector scales with the carrier density and the Bloch-Gruneisen temperature required density  dependence. At low temperature where optical phonon scattering is suppressed, scattering by  acoustic phonons become an important limiting factor for the mobility of the two dimensional  electron gas confined to the atomic layer of the extrinsic two dimensional semiconductors. We  have studied the acoustic phonon limited mobility of n-type semiconductor at low  temperatures taking into account both deformation potential and piezoelectric scattering. We  have calculated the deformation potential and piezoelectric interactions in two dimensional  semiconductors. Supported by continuum model calculations of the acoustic electron-phonon  interaction in two dimensional hexagonal lattices, this allowed establishing analytic  expressions and the individual coupling strengths for the two scattering mechanisms. The  calculated intrinsic low temperature mobility provided a platform for comparison with future  measurements of the carrier mobility in monolayer semiconducting compound. We have  found that mobility increased monotonically with carrier density. We have found that  mobility is substantially higher and showed much richer temperature dependence with higher  values of variation factor  and no linear temperature dependence. Our finding for the  acoustic electron-phonon interaction is also relevant in semiconductors. The obtained results  were found in good agreement with previously results.